Seleksi Jabatan Fungsional Umum Inspektur Bandar Udara Dengan Pendekatan Analytic Hierarchy Process (AHP) - Sutikno, Yusak; Saputra, Hendri (Universitas Katolik Parahyangan, 2024)
Airport Inspector is a strategic position responsible for carrying out technical guidance activities in regulation, control, supervision, investigation and operational safety services in the airport sector. Therefore, assessing and selecting personnel with appropriate abilities, competencies, and performance is essential to ensure that the right candidate fills this position so that services can be provided optimally. The current selection process is considered to be only administrative, does not reflect the expected competencies and performance, and is less transparent, so the results cannot be accounted for. This research solves this problem by optimizing the selection process using one of the Multi Criteria Decisions Method (MCDM) approaches, the AHP method, where this approach has never been used before. Through AHP, the selection process can be carried out in a more structured, objective, transparent, and intuitive manner as expected. This research optimizes the existing assessment criteria so that all parties can still accept the results: Formal Education, Competency, Years of Service, and Work Performance. The result shows that Work Performance has the highest weighting value (0.513), followed by Competency (0.267), Work Period (0.119), and Formal Education (0.101). The synthesis value of all criteria/sub-criteria shows that Candidate 3 is the highest (scale 1 of 1), then Candidate (0.742 of 1), Candidate 4 (0.726 of 1), and Candidate 1 is the lowest (0.665 of 1).